2006
DOI: 10.1080/07315724.2006.10719564
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Year Longitudinal Changes in Body Composition in Healthy Swiss Adults

Abstract: Weight change is clearly associated with a change in FFM. Weight gain is necessary to offset age-related FFM loss between 20 and 74 yrs. In active men, a FFM increase was associated with less weight gain than sedentary men. Future studies should evaluate the threshold of weight change and the level of physical activity necessary to prevent age-related losses of FFM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
2
22
0
3
Order By: Relevance
“…The results, which corroborated previous studies [4,6,8,12,13,22,24], indicated a clear negative association between level of physical activity and weight, and waist circumference and BMI values, in both genders. The more active a person was, the lower the values of these parameters.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results, which corroborated previous studies [4,6,8,12,13,22,24], indicated a clear negative association between level of physical activity and weight, and waist circumference and BMI values, in both genders. The more active a person was, the lower the values of these parameters.…”
Section: Discussionsupporting
confidence: 81%
“…A lifestyle factor known to be correlated with anthropometric parameters such as BMI, waist circumference, and weight is engagement in regular physical activity [4,6,8,12,13,22,24]. On the other hand, habitual physical activity is also known to be negatively correlated with some diseases [2,20].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, no statistically signifi cant linear correlation of BMI and body fat distribution with age was recorded, which has been recorded in other studies (Kyle et al, 2006), but only a slight proportional tendency of these two parameters with the age of respondents. Such a result can be explained by the fact that this is a pilot study which involved only about a hundred women, with approximately 70% of women being up to the age of forty, while 27% were older female respondents.…”
Section: Discussionmentioning
confidence: 59%
“…У овом истраживању није забележена ста-тистики значајна линеарна повезаност БМИ и заступњености масног ткива са годинама жи-вота, што се бележи у другим истраживањима (Kyle, et al, 2006), већ само блага пропорцио-нална тенденција ова два параметра са старошћу испитаница. Овакав резултат се може објаснити чињеницом да је ово пилот истраживање којим је обухваћено свега стотинак жена, при чему је при-ближно 70% жена било старости до четрдесет го-дина, а 27% су чиниле старије испитанице.…”
Section: дискусијаunclassified
“…Among those who gained weight at follow-up, the change in lean mass accounted for 32% of the weight change. 303 In another cohort of healthy volunteers 20 to 74 years old who were followed up for up to 3 years, almost half of the weight loss was because of loss in lean mass, and about half of the weight gain was attributed to change in lean mass. 304 Those relationships appeared to be independent of physical activity and age group.…”
Section: Assessing Changes In Body Compositionmentioning
confidence: 99%